BONE METABOLISM IN PATIENTS WITH SPINAL CORD INJURY - Selda Bağış; Günşah şahin; Canan Aybay; Aynur Karagöz (Archives of Rheumatology, 2002)
Osteoporosis is one of the complications of the spinal cord injury. Although enhancement of bone resorption after the injury has been demonstrated, increase of bone formation is controversial. In this study; 26 patients with spinal cord injury and 25 healthy volunteers were evaluated for the bone formation and resorption markers. Seventeen patients had paraplegia and nine patients had tetraplegia. American Spinal Injury Association (ASIA) score and functional independent measure (FIM) were used for the evaluation of the patients. Patients were divided into three groups according to ambulation level as bedridden, wheelchair dependent and walking with asistive devices. Total and ionized calcium, phosphorus, calcium excretion in 24-hour urine, urinary calcium/ creatinine ratio, alkaline phosphatase, parathormone, osteocalcine,C telopeptyde concentration were measured. Total and ionized calcium, parathormone and osteocalcine were found significantly lower in patients. Phosphorus, C telopeptyde, urinary calcium and calcium/ creatinine ratio were found significantly higher in patients compared to controls. Total calcium was lower in tetraplegic patients than paraplegic patients. Urinary calcium excretion and urinary calcium / creatinine ratio were found significantly higher in bedridden patients. Urinary calcium excretion was significantly higher in patients with ASIA score ≥50 and osteocalsine was higher in patients with ASIA score >50. In conclusion, we suggested that bone metabolism is different in spinal cord injury patients, bone formation does not equivalent bone resorption and related with the patient’s muscle strength and activity level.